Design of solar charging stations for electric bikes - Cordero Alvarado, Pablo Andrés (2020)
Renewable energies have an enormous potential in reducing emissions of petroleum-derived pollutants. As solar energy is the most abundant renewable energy on Earth, its utilization will be the guiding axis for the design proposal of this study, taking as main factors: the location of the stations, the tilt of the solar panels and the orientation of the photovoltaic system. The proposal of this study is a standard efficient solar charging station for electric bicycles, using the design of parameters for photovoltaic systems and the design of architectural; so, this prototype can be replicated anywhere in the world. The proposed design represents 339 liters of gas per year not consumed, which has an annual effect of 0,8 ton of carbon emitted to the environment.